Mechano-adaptable materials and structures for customizable electrochemical energy storage devices - Lv, Zhisheng (2019)
The ever-advancing electronic industry is reshaping our daily life with various flexible and customizable electronics, requiring electrochemical energy storage (EES) device with concreted flexibility and customizability to finish the entire packaging system. In this thesis, based on the mechano-adaptive electrode materials and device structures, three new kind of mechano-adaptive composite materials for strain enhancement, device editability and effective stress relief of material expansion during charging/discharging process are coupled with two kind of mechano-adaptable structures to achieved flexible EES devices with customizable structures, shapes and enhanced energy density.